Determination and analysis of the gene expression, involved in the differentiation and functioning of beta cells under the conditions of the development of experimental diabetes of the dexamethasone type (type 2 diabetes) - T. V. Ivanenko; A. V. Vynokurova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
According to the World Health Organization, the number of patients with diabetes is constantly increasing, making this issue relevant not only for medical science, but also for the healthcare system as a whole. The mechanisms of functioning and differentiation of beta cells of the pancreas have attracted significant scientific attention. Laboratory identification of the genetic mechanisms regulating these processes is crucial for understanding the molecular basis of the development of type 2 diabetes and for finding new approaches to its prevention and treatment.